Interleukin-13 and -4 expression in the central airways of smokers with chronic bronchitis - Miotto, D; Ruggieri, M.P; Boschetto, P; Cavallesco, G; Papi, A; Bononi, I; Piola, C; Murer, B; Fabbri, L.M; Mapp, C.E (The European respiratory journal, 2003)
The aim of this study was to determine whether the T‐helper 2‐type cytokines interleukin (IL)‐13 and ‐4 are involved in mucus hypersecretion, the hallmark of chronic bronchitis (CB). Surgical specimens were examined from 33 subjects undergoing lung resection for localised peripheral malignant pulmonary lesions: 21 smokers with symptoms of CB, 10 asymptomatic smokers (AS) and two nonsmokers with normal lung function. The number of IL‐4 and ‐13 positive (+) cells in the central airways was quantified. To better assess the cytokine profile, a count was also made of IL‐5+ and interferon (IFN)‐γ+ cells. Compared to AS, the CB group had an increased number of IL‐13+ and ‐4+ cells in the bronchial submucosa, while the number of IL‐5+ and IFN‐γ+ cells were similar in all the groups. No significant associations were found between the number of cells expressing IL‐13 or ‐4 and the number of inflammatory cells. Double labelling showed that 13.2 and 12.9% of IL‐13+ cells were also CD8+ and CD4+, whereas 7.5 and 5% of IL‐4+ cells were CD8+ and CD4+, respectively. In conclusion, T‐helper‐2 and ‐1 protein expression is present in the central airways of smokers and interleukin‐4 and ‐13 could contribute to mucus hypersecretion in chronic bronchitis.